Building with Steel : Details, Principles, Examples - Reichel, Alexander; Ackermann, Peter; Hentschel, Alexander; Hochberg, Anette (DETAIL Practice, 2012)
Detail Practice: Building with Steel is a handbook for quick, goal-oriented reading and implementation. Case study projects exemplify common norm details using large-scale drawings. The fundamentals of planning load-bearing structures provide design and planning help. This is supplemented by explanations of common load-bearing structures using examples of residential, office, hall and industrial buildings. Issues of fire safety and building physics particularly relevant to steel construction are treated alongside the use of steel as a material for cladding facades.